Etnobotânica, qualidade, compostos bioativos e atividade antioxidante do xique xique (Pilosocereus gounellei) em diferentes regiões da Paraíba - Silva, Antonia Almeida da (2017)
The family cactaceae due to its adaptive characteristics in the semiarid regions and its nutritional properties is used as forage, human food, medicinal and ornamental. The xique xique is a Cactus that fits in environments with high temperatures and low rainfall and the plant is used by the local population to many ends, including animal feed and medicinal. Some studies point to the use of xique-xique cladios to the production of sweets, flours to preparation of cuscuz, and few are those that treat of the utilization of the fruit in this category, being interesting the studies of this part of the plant that can identify the potentialities of the use. Ethnobotanical studies can identify more widely the use, utilization and the importance of this family according to the empirical knowledge of the region residents where this plant is originated. Besides that, studies that can identify the quality of fruits and the presence of natural antioxidants that can aggregate value to the species are necessary. Based on the above, the objective of this work was to identify the ethnobotanical use based in realized researches, quantity, bioactive compounds and antioxidants of the xique xique fruit (Pilosocereus gounellei) in different municipalities of the Paraíba Semiarid. According with ethnobotanical researches realized with Cactus, was identified diversity of category of the use to xique-xique, being the greatest use as forage, followed by feeding and construction. In general, the fruit pulp of xique-xique originated in Solânea and Boqueirão presented the greatest size being of interest to the more competitive markets. Both portions of fruit present source of bioactive compounds with antioxidant activity. The fruits from Solânea presented greater content polyphenols and betalains. In São Mamede the fruits presented superior functional potential due to high antioxidant activity.